TEORI VAN HIELE : TINGKAT BERPIKIR SISWA SMP BERGAYA KOGNITIF REFLEKSIF DAN IMPULSIF PADA MATERI SEGIEMPAT - Suci Apriyanti; Harina Fitriyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Thinking of geometry according to Van Hiele’s theory consist of 5 levels thatis level of visualization, analysis, informal deduction, deduction, and rigor.While the fast or not in responding to information is influenced by the reflective-impulsive cognitive style. This study aims to find out how the level of students thinking of reflective-impulsive cognitive style based on Van Hiele's theory on rectangular material.This research is descriptive qualitative research. Subjects in this study are 5 students of class VIII E in SMP N 4 Yogyakarta in academic year of 2016/2017 which each 2 students reflective and 3 students impulsive cognitive style. Technique of collecting data used MFFT, test (TBVH) and interview. Data analysis used Miles and Hubberman model.The results showed that the tendency of cognitive style of students is 66.69% reflective-impulsive cognitive style. The level of reflective subject thinking is at the analytical level while the impulsive subject is at the preanalysis level. The reflective subject has been able to give names of the quadrilateralbased on form and apparently and classify the characteristics of quadrilateral. While the impulsive subject has been able to give the names of the quadrilateral based on the form but still unable to classify itscharacteristics perfectly. Keywords: Van Hiele Theory, Cognitive Style, Reflective, Impulsive.